Sodium thiosulfate, a source of hydrogen sulfide, stimulates endothelial cell proliferation and neovascularization - Macabrey, Diane; Joniová, Jaroslava; Gasser, Quentin; Bechelli, Clémence; Longchamp, Alban; Urfer, Severine; Lambelet, Martine; Fu, Chun-Yu; Schwarz, Guenter; Wagnières, Georges; Déglise, Sébastien; Allagnat, Florent (Frontiers in Cardiovascular Medicine, 2022)
Therapies to accelerate vascular repair are currently lacking. Pre-clinical studies suggest that hydrogen sulfide (H2S), an endogenous gasotransmitter, promotes angiogenesis. Here, we hypothesized that sodium thiosulfate (STS), a clinically relevant source of H2S, would stimulate angiogenesis and vascular repair. STS stimulated neovascularization in WT and LDLR receptor knockout mice following hindlimb ischemia as evidenced by increased leg perfusion assessed by laser Doppler imaging, and capillary density in the gastrocnemius muscle. STS also promoted VEGF-dependent angiogenesis in matrigel plugs in vivo and in the chorioallantoic membrane of chick embryos. In vitro, STS and NaHS stimulated human umbilical vein endothelial cell (HUVEC) migration and proliferation. Seahorse experiments further revealed that STS inhibited mitochondrial respiration and promoted glycolysis in HUVEC. The effect of STS on migration and proliferation was glycolysis-dependent. STS probably acts through metabolic reprogramming of endothelial cells toward a more proliferative glycolytic state. These findings may hold broad clinical implications for patients suffering from vascular occlusive diseases.